Pengukuran Beban Kerja Fisiologis dan Psikologis pada Operator Pemetikan Teh dan Operator Produksi Teh Hijau di PTMitra Kerinci - Mega Mutia (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2014)
PT . Mitra Kerinci is agro-industry that have tea plantation and some factory facilities consist of tea processes, green tea processes and black tea processes. PT Mitra Kerinci become the largest green tea producer in Southeast Asia. The Company continually make improvements in every line of the company to produce high quality products. Workers are an important element of the company as well as a critical corporate asset. The company always keeping workers comfortable and maximal doing his job, for the activities associated with the production of green tea such as picking tea and green tea production process and should be evaluated and developed to be improved towards better way. This study aimed to measure the workload physiological and psychological workload on the operator plucking tea and green tea production operators and provide recommendations based on the results obtained to improve the work system at the plucking tea and green tea production PT Mitra Kerinci. Measurement of physiological workload done by calculating calorie requirements, CVLpercentage and consumption of each carrier by measuring the pulse and temperature measurement operator workload while the psychological conducted using the NASA-TLX.